Car cabin object detection using artificial intelligence (multimodal object detection) - Li, Ying (Nanyang Technological University, 2024)
Artificial intelligence has advanced tremendously in recent years, notably in areas such as computer vision. Object detection is a useful technique for tracking driver movements and improving road safety. Cameras can identify a wide range of objects, including people, computers, phones, infants, and many more, allowing us to alert drivers to potential safety hazards when they start to get fatigued or distracted.